Effect of Landscape Composition on Diversity and Abundance of Hymenoptera Parasitoids in Paddy Crops in Malang Regency, East Java - Aprilia, Setiya Dwi; Rizali, Akhmad (Journal of Tropical Plant Protection, 2026)
The existence of Hymenoptera parasitoids can be influenced by the landscape structure of agricultural land. Optimization of pest control using natural enemies can be done on a landscape scale. This study aimed to examine the characteristics of the rice cultivation landscape at each research location, examine the diversity of Hymenoptera parasitoids and their role in rice cultivation. In addition, this study aims to examine the factors that influence the diversity and abundance of Hymenoptera parasitoids, as well as examine the effect of landscape composition on the diversity and abundance of Hymenoptera parasitoids in rice cultivation in Malang Regency, East Java. The research was conducted at various designated rice planting locations. The research locations were in 4 sub-districts, namely Karangploso, Lawang, Kepanjen, and Tumpang sub-districts with three sampling points in each of these sub-districts. The research began with determining the location or ground survey. Insects were sampled using yellow pan traps,  with two traps installed in each subplot. Samples preserved in vials containing 70% alcohol were then sorted into microtubes according to sampling order, and specimens were examined morphologically to determine morphospecies. Supporting data were obtained from interviews with farmers or land owners. All data were entered into a database in Microsoft Excel and spreadsheets and analyzed using RStudio. The results indicated that the 12 study sites varied widely and were classified as complex landscapes, comprising eight land-use types dominated by natural habitats, paddy fields, and settlements. Hymenoptera parasitoids were found consisting of 8 families and 21 morphospecies. The parasitoids found act as parasitoids of eggs, larvae, eggs-larvae, and larvae-pupae. Altitude and age factors correlated with the diversity of Hymenoptera parasitoids. Landscape composition metrics, including Number of Patches (NP) and Class Area (CA) of rice fields, were correlated with the diversity and abundance of individual parasitoids.